[Notes from the tobacco Institute on airplane smoking restrictions] (Tufts Archival Research Center, 2007)
Notes from the Tobacco Institute regarding the issue of smoking on airplanes. Identifies its goals as preventing airlines from adopting smoking bans on their airplanes and mobilizing and organizing smokers. Lists its short term objectives, its target audience and the strategies they will employ to meet these objectives. Contains a section with random thoughts about the issue including its long term objective which is to create an environment in which more product can be sold.